Penggunaan Media Sosial dalam Portal Berita Online - Woro Harkandi Kencana; Ilona V Oisina Situmeang; Meisyanti Meisyanti; Khina Januar Rahmawati; Herlin Nugroho (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
The development of social media has now entered all fields, includingjournalism. Online news portals present news not only with websites andapplications but also using social media platforms. These social media include:Instagram, Facebook, Twitter, Youtube, and TikTok. This study wants to know theexistence of social media on online news portals. The online news portals that arethe object of research are: Liputan6.com, Medcom.id and iNews.id. This researchuses a qualitative approach with data collection techniques, conducting interviewswith news portal editors and making observations on the social media accounts ofthe three news portals. The result of this research is that online news portals usesocial media to find story ideas, establish engagement with their readers andviewers, and find additional information. While online news portals as a mediaindustry, make social media an interactive form of marketing and also provideadditional financial income for institutions.